Pengelolaan Unit Produksi Siswa Gajian Dalam Bidang Tata Busana Di SMK Muhammadiyah 5 Surakarta - Laila Nur Khasanah; Muhammad Fahmi Hanan; Wahyu Setianingsih; Muhammad Hajid Khoirullah; Mahasri Shobabiya (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
In accordance with article 15 UUSPN no. 20 of 2003 states that Vocational Schools are a type of formal education that aims to ensure that students are ready to enter the world of work and are able to prepare for life with independence. One of the efforts is to organize production unit management, namely combining business and academics. The aim of this research is to determine the management of the production unit for the salary student program at SMK Muhammadiyah 5 Surakarta. The method used is qualitative with a literature study approach. The result is the Payroll Student program. The aim is not to exploit students, but rather to train and improve students' abilities in accepting sewing orders from outside such as trousers, mukena bottoms, robes and negligees. The advantage of this salary student program is that you can increase your skills in sewing without having to buy fabric, and you can get a salary or wages from the orders the students get. Meanwhile, the downside is that students find it a little difficult to catch up on subjects they didn't follow when completing orders. However, there are teachers who do not force students to catch up.